Analisis Pengaruh Kinerja Keuangan dan Good Corporate Governance Terhadap Nilai Perusahaan Dengan Pengungkapan Corporate Social Responsibility Sebagai Variabel Mediating (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2010-2014) - S Depari, Frans Elkana; Wahyudi, Sugeng (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to examine the effect of the financial performance and corporate governance on corporate value with the disclosure of corporate social responsibility as a mediating variable. The dependent variable in this study is the value of a company that is proxied by Price Book Value, the independent variable is corporate governance and financial performance, as well as mediation variable is the social responsibility disclosure perususahaan.This study uses secondary data derived from the financial statements of companies listed on the Indonesia Stock Exchange 2010-2014. Total observation amounted to 121 companies. This study using purposive sampling method and to test hypotheses using multiple regression analysis and Sobel test with SPSS 21. Prior to the multiple regression analysis, first tested using classic assumption test.The results showed significant negative effect of managerial ownership to social responsibility, ROA is not insignificant to social responsibility, social responsibility is not significant to the ROA. Managerial ownership, ROA, social responsibility significant positive effect on firm value. In addition, social responsibility is not able to mediate the relationship between managerial ownership and corporate value and social responsibility are also unable to mediate the relationship between ROA and the value of the company.